PENINGKATAN KEMAMPUAN BAHASA MELALUI MEDIA AUDIO VISUAL PADA ANAK KELOMPOK A - Tuti Erlin; Atin Fatimah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
The objective of this action research is to improving language skills through audio visual media. Researcher observed young children’s from age four to five years using audio visual media and attempted to learn about their spontaneous language skills. The research was conducted at TK PGRI II Serang Banten. It was done in two cycles with reference to Kemmis and Taggart model. The result of this research are average value of children in language skills on pre-research 28%, then in cycle I increased to 41%, in cycle II experienced a significant increase of 70% and having success on indicators targeted.